Johann Ernst Gerhard (1621-1668) - Ben-Tov, Asaph. (Leiden ; Boston)
xii, 251 sayfa
Keywords: “In this biography of Johann Ernst Gerhard (1621-1668) Asaph Ben-Tov offers a study of a now forgotten yet unusually well documented seventeenth-century orientalist. Gerhard, the son of the famous Lutheran theologian Johann Gerhard, is not a towering figure but rather a fascinating representative of the academic culture of his day, especially of seventeenth-century Oriental studies. His extant Nachlassallows a close scrutiny of the life and work of an early modern scholar, focussing on his training, travels, the ambitious Harmonia linguarum Orientalium (1647) and other works, and the interests he fostered as a professor of history and theology in Jena. It aims to shed light on the broad and understudied field of Oriental studies in seventeenth century Germany“ --